The Influence of Revisit Intention Through E-WOM and City Branding in The Creative Tourism of The Ngarsopuro Night Market - Fadila, Sarah (LPPM Universitas Duta Bangsa Surakarta, 2023)
Various studies mention that tourists are currently changing their tourism travel patterns from buying products to buying experiences. From mass tourism to responsible tourism. Responding to changes in consumer / tourist demand from buying products to buying experiences and the growing need for responsible tourism, in terms of tourism, what is known as creativity-based tourism or creative tourism has emerged. Along with the development of tourism, especially cultural tourism, which not only places tourists as